Tree Health Monitoring of Risky Trees in the Hotel Open Space: A Case Study in Rancamaya, Bogor - Irfan Martiansyah; Rizmoon Nurul Zulkarnaen; Muhammad Rifqi Hariri; Prima Wahyu Kusuma Hutabarat; Fitri Fatma Wardani (Jurnal Sylva Lestari, 2022)
Tree health monitoring of risky trees is necessary, especially in areas with a high level of accessibility, such as in hotels and tourist areas. The increased accessibility of hotel visitors and the green space require increased awareness of the risk of falling trees. This research aimed to estimate the amount of internal decay and damage of living trees, with special attention to the large tree in the open space of R Hotel Rancamaya. Tree health monitoring was carried out using two approaches, namely visual observation Sonic Tomography method. The visual parameters were observed following the standard method of the International Society of Arboriculture. A total of 8 trees consists of four types of plants such as Melia azedarach, Durio zibethinus, Falcataria falcata, and Ficus subcordata. The eight trees visually showed no significant damage to their organs. The results of internal trunk inspection by PiCUS-3 Sonic Tomograph also showed a similar result with decay or weathering ranges ranging from 1-3% in healthy trees, except for the stem base of tree 7 (M. azedarach) with weathering of 18%. Handling that needs to be done on six trees at the green area hotel is through light pruning and installing warning signs so that visitors and staff are careful in the tree area. Substantial pruning is recommended specifically for tree 7 because there is significant weathering, and it could be dangerous if the tree is not appropriately handled. The assessment showed that mitigation, warning signs, and physical handling are essential to prevent any unpredicted fallen trees, especially for tree 3 (D. zibethinus) and tree 7 (M. azedarach). Keywords: hotel open space, risky trees, Sonic Tomography, tree health monitoring, visual observation